New insights into the pathways initiating and driving pancreatitis. Issue 5 (September 2016) - Gukovskaya, Anna S.; Pandol, Stephen J.; Gukovsky, Ilya
Abstract : Purpose of review: In this article, we discuss recent studies that advance our understanding of molecular and cellular factors initiating and driving pancreatitis, with the emphasis on the role of acinar cell organelle disorders. Recent findings: The central physiologic function of the pancreatic acinar cell – to synthesize, store, and secrete digestive enzymes – critically relies on coordinated actions of the endoplasmic reticulum (ER), the endolysosomal system, mitochondria, and autophagy. Recent studies begin to unravel the roles of these organelles' disordering in the mechanism of pancreatitis. Mice deficient in key autophagy mediators Atg5 or Atg7, or lysosome-associated membrane protein-2, exhibit dysregulation of multiple signaling and metabolic pathways in pancreatic acinar cells and develop spontaneous pancreatitis. Mitochondrial dysfunction caused by sustained opening of the permeability transition pore is shown to mediate pancreatitis in several clinically relevant experimental models, and its inhibition by pharmacologic or genetic means greatly reduces local and systemic pathologic responses. Experimental pancreatitis is also alleviated with inhibitors of ORAI1, a key component of the plasma membrane channel mediating pathologic rise in acinar cell cytosolic Ca2+. Pancreatitis-promoting mutations are increasingly associated with the ER stress. These findings suggest novel pathways and drug targets for pancreatitis treatment. In addition, the recent studies identify new mediators (e.g., neutrophil extracellular traps) of the inflammatory and other responses of pancreatitis. Summary: The recent findings illuminate a critical role of organelles regulating the autophagic, endolysosomal, mitochondrial, and ER pathways in maintaining pancreatic acinar cell homeostasis and secretory function; provide compelling evidence that organelle disordering is a key pathogenic mechanism initiating and driving pancreatitis; and identify molecular and cellular factors that could be targeted to restore organellar functions and thus alleviate or treat pancreatitis.